2017
DOI: 10.1111/his.13179
|View full text |Cite
|
Sign up to set email alerts
|

Global Gleason grade groups in prostate cancer: concordance of biopsy and radical prostatectomy grades and predictors of upgrade and downgrade

Abstract: We found highest concordance for GR2 and GR5 and lowest for GR4. The baseline clinical variables associated with GR1 upgrades and GR2 downgrades may play a role in clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
42
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 45 publications
4
42
1
2
Order By: Relevance
“…Actually, in China up to 50% of initially diagnosed prostate cancers are lethal disease, making curative treatment unavailable . An inherent limitation of the Partin table is the reliance on the most common combinations of PSA, clinical TNM classifications, and biopsies, which have come in for much criticism . In one series, 23.5% of clinical T3 tumors were found to have T2 disease at histopathology .…”
Section: Discussionmentioning
confidence: 99%
“…Actually, in China up to 50% of initially diagnosed prostate cancers are lethal disease, making curative treatment unavailable . An inherent limitation of the Partin table is the reliance on the most common combinations of PSA, clinical TNM classifications, and biopsies, which have come in for much criticism . In one series, 23.5% of clinical T3 tumors were found to have T2 disease at histopathology .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed this issue by comparing global GS and worst GS on biopsy with a number of endpoints, including radical prostatectomy findings and clinical follow‐up. These studies found that the two methods of reporting GS are comparable . A limitation of these studies is that the worst GS and global GS would be different in only a relatively small proportion of the cases.…”
mentioning
confidence: 97%
“…All these previous studies relate to patient cohorts, and may not be applicable to individual patients, because biopsy GS provides only an estimate of the GS in the prostate due to sampling variation, regardless of the methodology used to assign the GS . In a large series of 15 598 radical prostatectomy specimens, 22% of patients with biopsy GS 4 + 4 were found to have primary pattern 3 (3 + 3/3 + 4) on radical prostatectomy .…”
mentioning
confidence: 99%
See 2 more Smart Citations